Winners and Losers during the Great Recession: The Positive Impact of Marketing Expenditures. (November 2015) - Singh, Amrik; Dev, Chekitan S.
One of the factors that separated winning hotels from losers in the recession was the hotels' management of marketing expenses. By matching a group of 100 winners to 106 losers, based on high or low financial performance during the nadir of the recent recession, the study highlights the effects of marketing expenses as one primary driver of revenue and profit. The study compares the two groups' revenue and profitability metrics to determine the two groups' financial performance as the recession wore on. The results of this study show significant differences between winners and losers when measured by top-line indicators (Average Daily Rate [ADR], RevPAR, TRevPAR) and profitability (GOPPAR and NOIPAR). Winners were also found to spend significantly more on marketing than losers. The relationship between marketing expenditures and performance is significantly positive, with franchise expenses and other sales expenses emerging as the most important determinants of RevPAR, GOPPAR, and NOIPAR. In particular, these results highlight the importance of personal sales efforts, including promotions, familiarization trips, trade shows, and the training of sales personnel, personal sales visits to clients, and use of outside sales representatives to help hotels thrive in a recession. These data lead to the conclusion that firms that "invest" in marketing, especially in tough times, can achieve a payoff via various revenue drivers (e.g., trade shows) and will realize gains beyond just the short term.